An Educational Intervention on Situational Awareness and Understanding of Menstrual Hygiene, Knowledge, Taboo, and Its Practices among School-going Adolescent Girls in Rural Areas of Belagavi, Karnataka - Nagma Khan; Arati Mahishale (Archives of Medicine and Health Sciences)
Background and Aim: Menstruation is a normal physiological event for teenage girls who reach reproductive age. Superstitions and social taboos nevertheless surround it. An inadequate understanding of the menstrual cycle might lead to risky hygiene practices. Despite such clinical and educational impacts, menstruation-related information and hygienic behaviors are not adequately addressed in India, particularly among adolescent girls. Hence, the main objective of this study was to enhance adolescent schoolgirls’ knowledge and usage of menstrual hygiene management in the Belagavi District through educational intervention. Materials and Methods: Four eighty-four adolescent girls aged between 12 and 19 years were randomly assigned into the intervention group (IG group) and control group (CG group) (n = 242 per group). Both groups received one session of an educational intervention. Before and after the intervention, they were requested to complete outcome assessments using the Menstrual Knowledge, Sociocultural Restrictions and Barriers Questionnaire and Menstrual Practice Needs Scale-36. Results: The result of the study has revealed statistical significance. The IG group demonstrated an extremely significant change in both outcome measures’ preintervention and postintervention scores (P < 0.001). In comparison to the CG, the interventional group had superior postinterventional knowledge and hygiene practices, according to the between-group analysis (P < 0.001). Conclusion: According to the current research findings, knowledge levels significantly increased in the IG (88.8%) and the CG (28.45%). Adolescent girls’ practice scores also revealed a significant rise in the IG of 44.6% and no change in the CG. Thus, the educational program’s goals of enhancing menstrual hygiene understanding and practice were achieved effectively.